Prof. (Dr.) Hiralal Choudhuri - SHARMA, A P; Shrivastava, N P (Journal of the Inland Fisheries Society of India, 2021)
We salute and pay heartfelt homage to Prof. Hiralal Choudhuri, the ‘Diamond’ of the fisheries sector of India, who left us for his heavenly abode on 12th September, 2014. Dr. Choudhuri, the ‘Father of Induced Breeding’is also considered as the ‘Leader’ of blue revolution in India. To honour the great achievement of Dr. Choudhuri, the Government of India declared 10th July as National Fish Farmers Day since 2001.We feel proud that Dr. Choudhuri, a ‘Cifrian’ also happen to be a Life Member of the Inland Fisheries Society of India. The void created due to his passing away will never be filled up; it is a great loss to the entire fisheries fraternity of the country. He will always be in our hearts and remembered by all of us for his splendid work.